Recent advances on transition metal dichalcogenides for electrochemical energy conversion - Wu, Xin (2022)
Transition metal dichalcogenides (TMDCs) hold great promise for electrochemical energy conversion technologies in view of their unique structural features associated with the layered structure and ultrathin thickness. Because the inert basal plane accounts for the majority of a TMDC's bulk, activation of the basal plane sites is necessary to fully exploit the intrinsic potential of TMDCs. Here, recent advances on TMDCs-based hybrids/composites with greatly enhanced electrochemical activity are reviewed. After a summary of the synthesis of TMDCs with different sizes and morphologies, comprehensive in-plane activation strategies are described in detail, mainly including in-plane-modification-induced phase transformation, surface-layer modulation, and interlayer modification/coupling. Simultaneously, the underlying mechanisms for improved electrochemical activities are highlighted. Finally, the strategic evaluation on further research directions of TMDCs in-plane activation is featured. This work would shed some light on future design trends of TMDCs-based functional materials for electrochemical energy-related applications.